2018
DOI: 10.5897/ijbc2017.1123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of land use land cover changes using remote sensing Landsat images and pastoralists perceptions on range cover changes in Borana rangelands, Southern Ethiopia

Abstract: Studies on land-use/land cover (LULC) changes through remote sensing techniques represent vital tools for generating rational information for sound decision making on natural resources management. Related to the launching of the firstLandsat satellite in 1973 there is a region of attention on the use of remote sensing techniques as tool for planning the appropriate management in rangelands. This study therefore aimed at mapping LULC changes and identifying the associated changes that have occurred in the Boran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Common causes in eastern parts of Ethiopia particularly in Diredawa administration and Harari regional state were collection of woods for fuel consumption, population growth, agricultural expansion, charcoal production, livestock ranching and settlement expansion (Amisalu and Toru, 2018). Factors like farmland expansion, population pressure, deforestation and collection of woods for construction and charcoal production for fuel consumption, poor land tenure policy and land fragmentations have been significant driving factors in Southern Nations, Nationalities and Peoples Regional (SNNPR) state, central and southern Oromiya regional states (Berhan and Woldeamlak, 2014;Habtamu et al, 2018;Habtamu et al, 2017;Mikias, 2014;Gebrekidan et al, 2014;Hagos, 2014) Figure 2a and b. Driving factors prevailed in Tigray and Amhara regional states were associated with deforestations, high human and livestock population, charcoal production, agricultural expansion, prevalence of drought, resettlement (Samuale et al, 2014;Kebrom and Hedlund, 2000;Binyam et al, 2015;Miheretu and Yimer, 2017;Negasi et al, 2018;Mesfin et al, 2016;Worku and Csaplovies, 2015).…”
Section: Driving Factors Of Land-use/cover Change In Ethiopiamentioning
confidence: 99%
“…Common causes in eastern parts of Ethiopia particularly in Diredawa administration and Harari regional state were collection of woods for fuel consumption, population growth, agricultural expansion, charcoal production, livestock ranching and settlement expansion (Amisalu and Toru, 2018). Factors like farmland expansion, population pressure, deforestation and collection of woods for construction and charcoal production for fuel consumption, poor land tenure policy and land fragmentations have been significant driving factors in Southern Nations, Nationalities and Peoples Regional (SNNPR) state, central and southern Oromiya regional states (Berhan and Woldeamlak, 2014;Habtamu et al, 2018;Habtamu et al, 2017;Mikias, 2014;Gebrekidan et al, 2014;Hagos, 2014) Figure 2a and b. Driving factors prevailed in Tigray and Amhara regional states were associated with deforestations, high human and livestock population, charcoal production, agricultural expansion, prevalence of drought, resettlement (Samuale et al, 2014;Kebrom and Hedlund, 2000;Binyam et al, 2015;Miheretu and Yimer, 2017;Negasi et al, 2018;Mesfin et al, 2016;Worku and Csaplovies, 2015).…”
Section: Driving Factors Of Land-use/cover Change In Ethiopiamentioning
confidence: 99%
“…This causes environmental decline, including biodiversity loss and ecosystem disservice (Barana et al, 2016). Ayalew (2008), Tesfahun andTemesgen (2014), andHabtamu et al (2018) also discussed that the population dynamics and its associated problems to be major drivers of LULC change. Similarly, a study from Central Malawi reported that population growth, firewood collection, charcoal production, and poverty to be main drivers of LULC changes (Munthali et al, 2019).…”
Section: Perception On Lulc Dynamicsmentioning
confidence: 99%
“…Similarly, Barana et al (2016) discussed that conversion of forests and woodlands into cultivated land is chiefly due to the desire of land for crop production in order to satisfy the food demand to the ever growing human population, which terminated with the loss of land productivity and land degradation. Habtamu et al (2018) showed that the expansion of cropland in the Borana rangeland has meaningfully contributed to the change of grassland management practice into the cultivated land.…”
Section: Perception On Lulc Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies covering wider disciplines have been conducted in the area to contribute to the improved understanding of the ecological and socio-economic conditions for better management of the forest. Studies such as plant diversity and Ethnobotany (Kujawska et al, 2017), vegetation change (Habtamu, 2018), invasive woody plant species (Garuma and Wendawek, 2016) and socio-economic importance of Boke salt house (Wakshum et al, 2018), and population status and socio-economic importance of gum and resin bearing species (Adefris et al, 2012). However, most of these studies were made in the lowlands (rangeland and woodland) of Borana zone and only a few studies are made in the Arero forest to capture the relation between livelihoods, traditional forest management practices of communities in collaboration with formal (governmental and non-governmental) institutions and forest conditions.…”
Section: Introductionmentioning
confidence: 99%